In-situ growth flower-like binder-free 3D CuO/Cu2O-CTAB with tunable interlayer spacing for high performance lithium storage. Issue 2 (15th January 2023) - Lei, Xiaotong; Liu, Zhenjie; Ding, Juan; Cheng, Wenhua; Guo, Yong; Tang, Xincun; Wang, Bao; Huang, Yudai
Abstract: Copper-based oxides are attractive anode materials for lithium-ion batteries (LIBs) due to their abundant resources, low cost, non-toxic and high capacity. However, copper-based oxides will produce a huge volume change during lithiation/delithiation, and the structural strain caused by periodic volume changes may cause the exfoliation of active materials. Herein, a flower-like binder-free three-dimensional (3D) CuO/Cu2 O-CTAB was prepared by introducing CTAB, which homogeneously grew in situ on a copper mesh framework. The binder-free 3D sample guarantees direct contact between the active material and the copper mesh, maintaining the structure stability. The flower-like CuO/Cu2 O-CTAB with a small size reveals larger active interfaces and provides more active sites. The introduction of CTAB enlarges the interlayer spacing of CuO/Cu2 O, increases the active sites for lithium storage, and adapts to the volume change of the material during lithiation/delithiation. In addition, the expanded interlayer structure helps decrease the ion diffusion energy barrier for accelerating electrochemical reaction kinetics. Therefore, CuO/Cu2 O-CTAB exhibits better lithium storage performance (2.9 mAh cm −2 at 0.5 mA cm −2 ) than bare CuO/Cu2 O (1.8 mAh cm −2 at 0.5 mA cm −2 ). Graphical abstract: This work increases the lithium storage space by reasonably adjusting the interlayer spacing on the one hand, adapting to the volume change of the material during the lithiation/delithiation process, and on the other hand, enhancing the Li + diffusion kinetics. This provides a new strategy to alleviate the volume expansion problem of transition metal oxides during lithiation/delithiation. Image 1